2004
DOI: 10.1038/sj.cgt.7700798
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated p53 gene therapy in pediatric soft-tissue sarcoma cell lines: sensitization to cisplatin and doxorubicin

Abstract: Sarcomas, or tumors of connective tissue, represent roughly 20% of childhood cancers. Although the cure rate for sarcomas in general has significantly improved in the last 10 years, there continue to be subgroups that are difficult to treat. High-grade or metastatic soft-tissue sarcomas and rhabdomyosarcomas (RMS) of the extremities remain therapeutic challenges and their prognosis is often poor. The future of sarcoma therapy will likely include molecular approaches including gene/protein expression profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 70 publications
2
20
1
Order By: Relevance
“…Other possible determinants of the sensitivity to 2-DG are p53 and HIF-1, which regulate the glycolytic phenotype. p53 is not functional in any of the 3 sensitive alveolar rhabdomyosarcoma cell lines tested (29,30), which would agree with data that indicate that p53 protects cells from metabolic stress. However, RD cells are also deficient in p53 but still insensitive.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Other possible determinants of the sensitivity to 2-DG are p53 and HIF-1, which regulate the glycolytic phenotype. p53 is not functional in any of the 3 sensitive alveolar rhabdomyosarcoma cell lines tested (29,30), which would agree with data that indicate that p53 protects cells from metabolic stress. However, RD cells are also deficient in p53 but still insensitive.…”
Section: Discussionsupporting
confidence: 80%
“…Apoptosis induced by glucose deprivation in hematopoietic cells is inhibited by overexpression of Bcl-2 or Bcl-x L , and it has been shown to be mediated by Noxa, Puma, or Bim (20,25). We could not detect induction of Puma, possibly because this protein is usually induced in a p53-dependent manner, but the alveolar rhabdomyosarcoma cells used in this study are deficient in p53 (29,30). Consistent with data that suggest that death induced by 2-DG is due to ER stress, we observed induction of Bim, which mediates death induced by ER stress in some systems (37).…”
Section: Discussioncontrasting
confidence: 46%
“…We observed that all cell lines tested were resistant to hypoxia-induced apoptosis (Figure 1a). For further experiments we selected a p53 wild type (A204 RMS) and a p53-deficient (A673 ES) cell line (Ganjavi et al, 2005). Additionally, analysis by flow cytometry using Annexin V-fluorescein isothiocyanate (FITC)/ propidium-iodide (PI) double staining revealed that hypoxia also did not induce necrotic cell death in both A204 RMS and A673 ES cells (Figure 1b).…”
Section: Resistance Of A204 Rms and A673 Es Cells To Hypoxiainduced Amentioning
confidence: 99%
“…Mutations in the p53 gene are among the most frequent somatic genetic changes observed in human cancers, and consequently, p53 mutational status has been extensively studied for its correlation with tumor grade, patient survival, and treatment outcome in many cancers (10). The results of these studies have, however, been inconsistent with some showing a positive correlation of p53 mutations with tumor growth, progression, and drug resistance (11)(12)(13)(14), whereas others showed the mutant p53 status to be deleterious to survival and to favor drug sensitivity (15)(16)(17). The findings indicate a high level of complexity in the role of p53 in human cancer and suggest that multiple upstream and downstream pathways of p53 may interact to mediate its effects in this disease.…”
Section: Introductionmentioning
confidence: 76%